Effects of helical centerline stent vs. straight stent placement on blood flow velocity - Kohata, Yutaro; Ohta, Makoto; Jin, Kazuyoshi; Anzai, Hitomi (Frontiers in Medical Technology, 2023)
As an approach to maintain patency in femoropopliteal stenting, a helical stent configuration was proposed, which showed improved patency in clinical trials. However, the effects of helical stent placement on the flow have not been quantitatively analyzed. The purpose of this study was to estimate flow velocities to quantify the influence of helical stent placement. Helical and straight stents were implanted in three healthy pigs, and the flow velocities were estimated using the time-intensity curve (TIC) in the angiography images. The angiographic images indicated thinning of the leading edge of the contrast medium through the helically deformed artery, which was not observed in the straight stent. The slower rise of the TIC peak in the helical stent indicated faster travel of this thinner edge. Arterial expansion due to stenting was observed in all cases, and the expansion rate varied according to location. All cases of helical stent implantation showed that velocity was maintained (55.0–71.3% velocity retention), unlike for straight stent implantation (43.0–68.0% velocity retention); however, no significant difference was observed.